Chemoselective dithioacetalization of aldehydes using silica sulfuric acid as a reusable catalyst - Pore, D. M.; Desai, Uday V.; Mane, R. B.; Wadgaonkar, P. P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2006)
Silica sulfuric acid has been found to be an efficient and reusable catalyst for chemoselective dithioacetalization of aldehydes over ketones, in excellent yields.
Keywords: Chemoselective; dithioacetalization; silica sulfuric acid

Characterization of clay intercalated cobalt-salen catalysts for the oxidation of p-cresol - Kshirsagar, V. S.; Garade, Ajit C.; Mane, R. B.; Patil, K. R.; Yamaguchi, A.; Shirai, M.; Rode, C. V. (Applied Catalysis A-General, 2009)
The intercalation of cobalt-salen complexes into the interlamelar spaces of montmorillonite clay was investigated by various characterization studies. The ``neat'' cobalt-salen complex showed a weight loss at 368 degrees C while the weight loss for the corresponding intercalated complex was observed at much higher temperature of 492 degrees C due to decomposition of the complex. The thermal stabilization observed was due to the host-guest interaction of clay and metal complex and thus confirmed the intercalation. The XANES spectrum of Co(salen)-mont sample revealed the change of symmetry from the tetrahedral in plane to the octahedral structure having an axial bonding of oxygen to the cobalt, indicating that cobalt atoms in Co(salen)-mont were coordinated axially with the lattice oxygen of montmorillonite. Both XANES and EXAFS results indicated that cobalt atoms in Co(salen)-mont form two additional Co-O bonds with a bond length of 0.199 nm by the intercalation while retaining the Co-salen structure. Co-salen intercalated into the montmorillonite clay showed the highest activity for the air oxidation of p-cresol, giving 88% selectivity to the oxidation products. Effects of NaOH concentration and various solvents on the conversion and selectivity patterns also have been studied. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cobalt-oxygen bond; Cobalt-salen; Extended X-ray absorption fine structure; Intercalation; Lattice oxygen; Montmorillonite; X-ray absorption near edge structure

Acidity tuning of montmorillonite K10 by impregnation with dodecatungstophosphoric acid and hydroxyalkylation of phenol - Garade, Ajit C.; Kshirsagar, V. S.; Mane, R. B.; Ghalwadkar, Ajay A.; Joshi, U. D.; Rode, C. V. (Applied Clay Science, 2010)
Acidity tuning of montmorillonite K10 (mont K10) was achieved by impregnating with dodecatungstophosphoric acid (DTP). The effect on the hydroxyalkylation of phenol was studied at 353 K with phenol to formaldehyde molar ratio of 5. The nature and strength of acid sites were determined by NH(3)-TPD measurement while the distribution of Brensted and Lewis acid sites expressed as B/L ratio, was determined by pyridine IR technique. Among various loadings of DTP (5-60%) studied for the hydroxyalkylation of phenol, 20% DTP/mont K10 showed the highest catalyst activity (90% selectivity to bisphenol F with 28% conversion of phenol). Both total concentration of acid sites and the distribution of acid sites in a high temperature region were required for the high bisphenol F selectivity. Our catalyst (20% DTP/Mont K10) could be recycled three times. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acidity tuning; Dodecatungstophosphoric acid/Montmorillonite K10; Hydroxyalkylation; Impregnation; Temperature programmed desorption

Selective hydrogenolysis of glycerol to 1,2-propanediol: comparison of batch and continuous process operations - Rode, Chandrashekhar V; Ghalwadkar, Ajay A.; Mane, R. B.; Hengne, Amol M.; Jadkar, Sachin T.; Biradar, Narayan S. (Organic Process Research & Development, 2010)
The screening of copper chromite catalysts with various promoters such as Al, Zn, and Ba for glycerol hydrogenolysis to 1,2-propanediol (1,2-PDO) in a batch reaction showed that Cu-Cr (Ba) catalyst gave the highest conversion of 34% and selectivity of 84% to 1,2-PDO. In a continuous operation (23 g catalyst bed) the same catalyst showed higher conversion of glycerol and selectivity for 1,2-PDO of 65% and > 90%, respectively, with an on-stream activity of similar to 800 h. Better performance in a continuous operation could be due to the in situ activation of the catalyst, suppression of glycerol cracking to ethylene glycol, as well as excessive hydrogenation of 1,2-PDO to 2-propanol due to lower contact time of 1.3 h as compared to that in a batch operation (5 h). Effects of various process parameters on conversion and selectivity also have been compared for batch and continuous operations.

Role of promoters in copper chromite catalysts for hydrogenolysis of glycerol - Mane, R. B.; Ghalwadkar, Ajay A.; Hengne, Amol M.; Suryawanshi, Y. R.; Rode, C. V. (Catalysis Today, 2011)
Various copper chromite catalysts with and without promoters were prepared by simultaneous co-precipitation and digestion technique and the role of promoters (Al, Ba and Zn) was investigated for hydrogenolysis of glycerol to 1,2-propylene glycol (1,2-PG) in both batch and continuous operations. Among various promoters studied, copper chromite catalyst with Ba as a promoter showed the highest activity and selectivity of 85% to 1,2-PG. This catalyst was found to be active for more than 800 h in a continuous operation also. Ammonia TPD results showed that barium promoted copper chromite catalyst had the highest acidity which facilitates the dehydration of glycerol to acetol which is the first step in hydrogenolysis of glycerol to 1,2-PG. The effect of barium content and variation in the promoters combination was also studied. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: 1; 2-Propylene glycol; Acetol; Ammonia TPD; Glycerol hydrogenolysis; Surface acidity

Copper modified waste fly ash as a promising catalyst for glycerol hydrogenolysis - Rode, C. V.; Mane, R. B.; Potdar, A. S.; Patil, P. B.; Niphadkar, P. S.; Joshi, P. N. (Catalysis Today, 2012)
Several catalyst formulations using waste fly ash along with Cu were prepared and characterised by XRD, BET and TEM. These catalysts were also evaluated for the first time for hydrogenolysis of glycerol to 1,2 propanediol (1,2-PDO) in a batch reactor under 52 bar H-2 pressure in the temperature range of 473-513 K conditions. The fly ash pretreated by alkali using the fusion method and impregnated with Cu showed higher activity and stability for glycerol hydrogenolysis. Due to pretreatment with alkali at high temperature, transformation of alpha-quartz to the tridymite phase of SiO2 occurred. More importantly, use of alkali either during the pretreatment or the Cu loading step resulted in a high dispersion on the surface which was responsible for higher glycerol conversion and 1,2-PDO selectivity. The effects of temperature, Cu loading and solvent on glycerol conversion and product selectivities were also studied in this work. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1; 2-Propanediol; Alkali fusion; Cu loading; Fly ash; Glycerol hydrogenolysis

Effect of preparation parameters of Cu catalysts on their physico-chemical properties and activities for glycerol hydrogenolysis - Mane, R. B.; Kondawar, S. E.; Niphadkar, P. S.; Joshi, P. N.; Patil, K. R.; Rode, C. V. (Catalysis Today, 2012)
Cu based catalysts were prepared by co-precipitation, alkali fusion followed by precipitation and direct solid state fusion methods. The changes in the phase formation, morphology, crystallite size, extent of aggregation, strength and nature of acid sites were observed due to variations in precipitating agents and also their order of addition. The catalyst prepared by co-precipitation using Na2CO3 showed the predominant presence of metallic Cu phase with a crystallite size of 5 nm, well segregated spherical morphology and highest acidity in the activated sample. These intrinsic properties contributed to achieve the highest glycerol conversion of 62% and 1,2-PDO selectivity of 88% in glycerol hydrogenolysis. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Co-precipitation; Cu catalysts; Glycerol hydrogenolysis; Physico-chemical properties; Solid state fusion

Carbonylation of glycerol with urea to glycerol carbonate over supported Zn catalysts - Kondawar, S. E.; Mane, R. B.; Vasishta, A.; More, S. B.; Dhengale, S. D.; Rode, C. V. (Applied Petrochemical Research, 2017)
Glycerol carbonylation with urea is a very feasible option to produce glycerol carbonate with a net result of CO2 fixation through urea synthesis. The prerequisite of an efficient catalyst for this reaction is to possess both acid and basic sites together. Several acidic supports were screened for ZnO catalyst in this work and Zn/MCM-41 was found to exhibit the best activity and almost complete selectivity to glycerol carbonate (GC). Although, non-catalytic glycerol carbonylation resulted in GC formation but glycerol conversion achieved was twice with Zn/MCM-41 as a catalyst. Further to that increase in Zn loading from 2 to 5% resulted in increase in glycerol conversion from 63 to 82%. The prepared catalysts were characterized by XRD, NH3 and CO2-TPD and effects of reaction parameters such as catalyst loading, glycerol to urea mole ratio and temperature on glycerol conversion and GC selectivity in batch mode of operation were also studied. Time on stream activity of 5% Zn/MCM-41 catalyst for continuous carbonylation of glycerol was also studied for ~100 h with an average conversion of ~55% and complete selectivity to GC. This indicated five times lower productivity of GC per h due to lower residence time than that in a batch operation as compared to that of a continuous operation. Activation energy estimated from the Arrhenius plot was found to be 39.82 kJ mol−1 suggesting that the reaction is kinetically controlled. A reaction pathway mediated by acid and basic sites of the Zn/MCM-41 catalyst is also proposed.
Keywords: Acid–base ratio; Continuous process; Glycerol carbonate; Glycerol-urea carbonylation; reaction pathway; Supported Zn; Zn loading

Catalytic ozonation of clofibric acid over copper-based catalysts: in situ ATR-IR studies - Sable, Shailesh S.; Ghute, P. P.; Fakhrnasova, D.; Mane, R. B.; Rode, Chandrashekhar V.; Medina, F.; Contreras, S. (Applied Catalysis B-Environmental, 2017)
The current study describes the catalytic ozonation of clofibric acid (CFA) under ambient conditions using copper oxide catalysts synthesized by different methods. The objective of this study is to provide novel catalysts and reaction mechanism for the degradation of emerging pharmaceutical compounds in aqueous solution. Among the various Cu catalysts screened in this study, the Cut-Ali oxide catalyst showed an excellent activity and stability in the degradation and mineralization of CFA. In situ attenuated total reflection IR (ATR-IR) spectroscopy was used to examine the interaction of ozone with the active sites of the catalyst in presence of water and to investigate the possible catalytic mechanism. The presence of Lewis acid sites in the Cut-Ali catalyst increased the amount of chemisorbed water enhancing stronger interaction of ozone to form surface activated species, resulting in higher catalytic activity. The results obtained from in-situ ATR-IR study indicate that surface hydroxyl groups and Lewis acid sites are responsible for promoting the generation of hydroxyl radicals (OHS) from aqueous ozone. (C) 2017 Elsevier B.V. All rights reserved.